The assesment of trigger points (TrPs) apperiance in masticatory muscles and cervical spine in patients with stomatognathic system (SS) disorders- preliminary reports - Gębska, Magdalena; Weber-Nowakowska, Katarzyna; Mikołajczyk-Kocięcka, Anna; Garczyński, Wojciech (Journal of Education, Health and Sport, 2019)
Introduction: Increased tension around masticatory muscles can cause pain disorders in facial part of the skull, temporomandibular joint, supra- and infrahyoid area and cervical spine. Unphisiological muscle work bring up Trigger Points (TrPs). The consequences is heterotropic pain. Aim: The objective of the study was the assesment of Trigger Points (TrPs) apperiance in masticatory muscles and cervical spine in patients with myogenic disorders in stomatognathic system. Material and Methods: 135 female (age 20 – 45 years old) diagnosed with myogenic disorders in stomatognathic system and pain in facial part of the skull were assesed. Physical examination were conducted: medical interview, assesment of Trigger Points (TrPs) apperiance in masticatory muscles and cervical spine. Results: All patients had pain disorders in facial part of the skull, and reported increased tension in masticatory muscles. 98% had cervical spine pain disorders. All women had increased palpatic tenderness in masticatory muscles and cervical spine. The number of Trigger Points (TrPs) in supraficial head of masseter muscle was similar to the number of TrPs in sternocleidomastoid muscle of the same side of the body.